An Integrative Analysis of Meningioma Tumors Reveals the Determinant Genes and Pathways of Malignant Transformation - Iglesias Gómez, José Carlos; Mosquera Orgueira, Adrián (Frontiers in Oncology, 2014)
Meningiomas are frequent central nervous system neoplasms which despite their predominant benignity, show sporadically malignant behaviour. Type 2 Neurofibromatosis and polymorphisms in several genes have been associated with meningioma risk and are probably involved in its pathogenesis. Although GWAS studies have found loci related to meningioma risk, little is known about the factors determining malignant transformation. Thus, this study is aimed to identify the genomic and transcriptomic factors influencing evolution from benignity towards aggressive phenotypes. By applying an integrative bioinformatics pipeline combining public information on a wealth of biological layers of complexity (from genetic polymorphisms to protein interactions), this study identified a module of co-expressed genes highly correlated with tumor stage and statistically linked to several genomic regions (module Quantitaive Trait Loci, mQTLs). Ontology analysis of the transcription hub genes identified microtubule-associated cell cycle processes as key drivers of such network. mQTLs and SNPs associated with meningioma stage were replicated in an alternative meningioma cohort, and integration of these results with up-to-date scientific literature and several databases retrieved a list of genes and pathways with a potentially important role in meningioma malignancy. As a result, cytoskeleton and cell-cell adhesion pathways, calcium channels and glutamate receptors, as well as oxidoreductse and Endoplasmic Reticulum Associated Degradation (ERAD) pathways were found to be the most important and redundant findings associated to meningioma progression. This study presents an integrated view of the pathways involved in meningioma malignant conversion and paves the way for the development of new research lines that will improve our understanding of meningioma biology.